2006
DOI: 10.1074/jbc.m511100200
|View full text |Cite
|
Sign up to set email alerts
|

CpG Sites Preferentially Methylated by Dnmt3a in Vivo

Abstract: Dnmt3a and Dnmt3b are two major de novo DNA methyltransferases essential for embryonic development in mammals. It has been shown that Dnmt3a and Dnmt3b have distinct substrate preferences for certain genomic loci, including major and minor satellite repeats. However, the exact target CpG sites where Dnmt3a and Dnmt3b catalyze DNA methylation remains largely unknown. To identify a CpG site that is specifically methylated by Dnmt3a or Dnmt3b, we screened methylated genomic loci by methylation sensitive restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 35 publications
(49 reference statements)
2
36
0
Order By: Relevance
“…The other differentially methylated CpG islands resided either inside genes or in nongenic regions. For promoter-associated CpG islands, a number of them, including those of NTF3, FGF, OSR1, HOXA6, NPY and WT1, have previously been reported as differentially methylated in other cancer types (Mares et al, 2001;Bibikova et al, 2006;Oka et al, 2006;Houshdaran et al, 2007;Illingworth et al, 2008). Our study also identified many CpG islands that were not previously shown to be differentially methylated, such as CXCL5, EID1 and TRHDE.…”
Section: Differentially Methylated Cpg Islands and Promoterssupporting
confidence: 62%
“…The other differentially methylated CpG islands resided either inside genes or in nongenic regions. For promoter-associated CpG islands, a number of them, including those of NTF3, FGF, OSR1, HOXA6, NPY and WT1, have previously been reported as differentially methylated in other cancer types (Mares et al, 2001;Bibikova et al, 2006;Oka et al, 2006;Houshdaran et al, 2007;Illingworth et al, 2008). Our study also identified many CpG islands that were not previously shown to be differentially methylated, such as CXCL5, EID1 and TRHDE.…”
Section: Differentially Methylated Cpg Islands and Promoterssupporting
confidence: 62%
“…Altered expressions of DNMTs have been linked to the cancer-associated hypermethylation of TSGs (Gius et al, 2004;Suzuki et al, 2004;Pruitt et al, 2005;Oka et al, 2006), as well as the hypomethylation of melanoma antigen gene MAGE-A1 (Loriot et al, 2006). We sought to determine which DNMT was involved in CSE-induced changes in the methylation pattern of SNCG.…”
Section: Cigarette Smoke Differentially Regulates Dnmts In A549 Cellsmentioning
confidence: 99%
“…It was shown that inactivation of DNMT3B in mouse embryonic fibroblasts resulted in DNA hypomethylation, chromosomal instability and spontaneous immortalization, but these changes were not observed by inactivating DNMT3A (Dodge et al, 2005). Another recent study reported that the first exon of the G isoform of fibroblast growth factor is the preferred substrate for DNMT3A but not for DNMT3B (Oka et al, 2006). Our results in this study further show that these two enzymes are under different regulation by CSE, and that the CpG island of SNCG is a specific substrate of DNMT3B not DNMT3A.…”
Section: Synuclein-c Is a Target Gene Of Dnmt3bmentioning
confidence: 99%
“…14,15 DNA methylation patterns are established by three independent DNA methyltransferases-DNMT1, DNMT3A, and DNMT3B 16,17 -known to be necessary during neural progenitor cell development. [18][19][20] DNMT1 is mainly implicated in Purpose: Hirschsprung disease (OMIM 142623) is a neurocristopathy attributed to a failure of cell proliferation or migration and/or failure of the enteric precursors along the gut to differentiate during embryonic development. Although some genes involved in this pathology are well characterized, many aspects remain poorly understood.…”
Section: 2mentioning
confidence: 99%